A Beginner's Guide to Water Management—Oxygen and Temperature - Florida LAKEWATCH; Mark Hoyer (EDIS, 2004)
This document, CIR109, is the seventh of a series of information circulars dedicated to familiarizing citizens with the language and techniques used by those involved in water management.  June 2004 1st Edition.